The Determinants of Salary and Bonus for Rank and File Employees - Dominique M. Demougin; Oliver Fabel (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 2004)
The current study integrates the repeated game approach to implicit contracts and the analysis of explicit bonus rules based on subjective performance evaluation to determine the optimal structure of the compensation scheme for the average white- collar employee. In contrast to previous contributions we assume that the agent is risk-neutral but liquidity constrained. The salary reflects the maximum reward associated with contractual compliance which can be implicitly agreed. If the probability that the employee remains within the firm increases, the principal can reduce the rent captured by the agent. Hence, the optimal salary increases and the bonus decreases. Nevertheless, the optimal effort supply unambiguously increases.
urn:nbn:de:bsz:352-opus-13044
Keywords: M52; 330; White-Collar Employees; Implicit Contract; Explicit Bonus; Reputational Equilibrium; Anreizvertrag; Leistungsanreiz; Vertrag; Agency Theory; Wiederholte Spiele; Theorie